The mediating influence of service failure explanation on customer repurchase intention through customers satisfaction - Tarofder, Arun Kumar; Nikhashemi, Seyed Rajab; Azam, S.M. Ferdous; Selvantharan, Prashantini; Haque, A. K. M. Ahasanul (Emerald Publishing, 2016)
Purpose – The purpose of this paper is to examine the effect of explanation on customer satisfaction in the service failure stage. It seeks to better understand the dynamics of consumer repurchase intention through a mediating effect of customer satisfaction. Design/methodology/approach – A structured questionnaire was e-mailed to collect the primary data. With three reminders, this study managed to obtain 322 responses from customers who complained about their internet service in Malaysia. Structural equation modelling techniques were applied to examine both direct and mediating effects between variables. Findings – Results reveal that all four dimensions of explanation have significant partial mediating effect on repurchase intention through customer satisfaction. Results also disclose that there is no significant relationship between excuse and customer satisfaction in service failure. Among all dimensions, reference and apology have higher influence on repurchase intention through customer satisfaction. Research limitations/implications – The results are particularly valuable for managers, as it supports the role of using explanation as a practical tool for fostering positive and profitable outcomes like repeat customer purchases. Practical implications – The findings of this study will help organisations rethink their explanation strategies with the eye to foster greater customer repurchase intention. Originality/value – The results are particularly valuable for managers, as they support the role of using explanation as a practical tool for fostering positive and profitable outcomes like repeat customer purchases.